Benchmarking the Governance of Tertiary Education Systems - World Bank (Washington, DC, 2015)
This paper presents a benchmarking approach for analyzing and comparing governance in tertiary education as a critical determinant of system and institutional performance. This methodology is tested through a pilot survey in East Asia and Central America. The paper is structured in the following way: (i) the first part highlights the link between good governance practices and the performance of tertiary institutions (ii) the second part introduces the analytical approach underpinning the governance dimensions of the benchmarking tool and the specific indicators that could be used to develop relevant governance databases; (iii) the third and final part presents the results of two pilot surveys carried out by the World Bank in the East Asia and Central America regions in relation to the governance of the tertiary education systems and institutions of the countries concerned.